Haunted Selves, Haunting Places in English Literature and Culture - Wolfreys, Julian. author. aut Link
X, 258 p.
Keywords: Haunted Selves, Haunting Places in English Literature and Culture offers a series of readings of poetry, the novel and other forms of art and cultural expression, to explore the relationship between subject and landscape, self and place. Utilizing an interdisciplinary approach grounded in close reading, the text places Jacques Derrida’s work on spectrality in dialogue with particular aspects of phenomenology. The volume explores writing and culture from the 1880s to the present day, proceeding through four sections examining related questions of identity, memory, the landscape, and our modern relationship to the past. Julian Wolfreys presents a theoretically informed understanding of the efficacy of literature and culture in connecting us to the past in an affective and engaged manner.